Exploring the Mechanism of Antioxidant Action of Bitter Almond Based on Network Pharmacology and Molecular Docking Techniques - Xuehua Feng; Jingya Niu; Zurong Song; Ali Tao; Rumin Zong; Wenqing Pei; Panpan Gong (Journal of Food Quality)
Objective. A network pharmacology approach was used to investigate the main active ingredients, key targets, and mechanisms of action of bitter almond antioxidants, and preliminary validation of the relevant targets was performed using molecular docking techniques. Methods. The active ingredients of bitter almond were obtained through the traditional Chinese medicine systematic pharmacology database and analysis platform (TCMSP), and the main active ingredients were screened by bioavailability (OB) and drug-like properties (DL); the GeneCards database was used to search antioxidant-related disease targets through the traditional Chinese medicine systematic pharmacology database and analysis; building a “drug-disease-target” visual network map with Cytoscape 3.9.0 software; a protein interaction (PPI) network was constructed using STRING website and core targets were screened; GO function and KEGG pathway enrichment analysis were obtained using Metoscape. Finally, SailVina software was used to molecularly dock the major active ingredients and target proteins and visualize them using PyMOL software. Results. A total of 19 antioxidant active ingredients were obtained for bitter almond, mainly stigmasterol, glycyrol, and estrone. The targets regulated by their main active ingredients were intersected with oxidative targets, and 53 intersected targets were obtained by Venn diagram, with key targets involving NR3C2, NCOA2, MAOA, ADRA2A, and CHRM1; GO analysis yielded 3616 GO entries, including 2821 biological process (BP) entries, 316 cellular component (CC) entries, and 479 molecular function (MF) entries, and 184 signalling pathways were obtained from KEGG pathway enrichment screening. The molecular docking results showed that Stigmasterol-NR3C2 binding was better. Conclusion. Stigmasterol, glycyrol, estrone, and licochalcone B in bitter almond may be the material basis of antioxidant and have better antioxidant activity; therefore, bitter almond has the characteristics of multicomponent, multitarget and multipathway.